STRATEGI PENGAMBILAN KEPUTUSAN DALAM PEMECAHAN MASALAH (STUDI KASUS PADA BANK XYZ CABANG TAJUR HALANG CIANJUR JAWA BARAT) - Mukhtadi Mukhtadi; Mohammad Rizki (Universitas YARSI, 2019)
Competition in the business world is increasingly tight. This is also felt by businessman in the banking sector who are required to have a better quality of service so as to satisfy customers satisfaction. Bank XYZ is a private bank with branch offices in Tajurhalang Cianjur, West Java. This research aims to analyze Service Quality Bank XYZ Branch of Tajurhalang Cianjur, West Java, with Service Quality dimension, Tangible, Emphaty, Realibility, Responsiveness, Assurance, Layout using the Fishbone Diagram method. By using the fishbone diagram we will know the problems being faced based on the analysis. then will be made a decision making based on the group